Nonlinear control of a grid connected hybrid energetic systems (HES) based on photovoltaic-fuel cells distributed power generation systems - Khoudiri, Said; Benchabane, Fateh; Yahia, Khaled (Journal of Applied Engineering Science & Technology, 2018)
This paper presents a discrete-time integral sliding mode control for a grid connected hybrid energetic systems (HES) based on photovoltaic-Solid oxide fuel cell (SOFC) for distributed power generation systems. The proposed HES systems employ solid oxide fuel cell (SOFC) and photovoltaic panels as main sources, supercapacitors as complementary sources, and controlled DC-DC boost converter and three levels NPC inverter. A maximum power point tracking (MPPT) control is used in order to maximize the power of the photovoltaic system. The proposed control consists of a power management grid interface inverter transferring the energy from the hybrid sources into the grid by controlling the main utility grid and the common DC voltage active and reactive power. The obtained simulation results show the effectiveness and robustness of the proposed control strategy. Keywords: Hybrid Energetic Systems (HES), Solid Oxide Fuel Cell (SOFC), Photovoltaic (PV), Sliding Mode Control, Maximum Power Point Tracking (MPPT), Grid power management.